Diagnostic Imaging Fundamentals: Head Trauma - Jorge Lee Diaz; Roy Riascos; Robert Jackson; David Clifton; Rami Eldaya (Association of American Medical Colleges, 2015)
Abstract We have created a didactic tool for early radiology and nonradiology trainees that facilitates the approach to image interpretation for given clinical questions from the ground up. This team-based learning (TBL) module is designed to provide residents with a brief and straightforward guide to the interpretation of imaging studies for patients with head trauma. It is intended for use by first-year radiology residents but can also be used to train neurosurgery and emergency medicine residents as well. The module was developed in 2013 and improved in 2014 with the addition of new cases. It is part of an ongoing project consisting of multiple modules developed to introduce a systematic approach for different complaints/scenarios. Learning involves preclass reading, in-class readiness assurance exercises, and group application exercises. All the students are evaluated using the Readiness Assurance Test before the class starts. The score of the test is not intended to evaluate the student but to help the evaluator designate equally balanced groups of three to five students who can teach and help each other during the group application exercises. We presented this TBL module to first-year residents from an academic university program, and 100% of them were satisfied with the session. Although we do not have specific quantitative data about the outcomes of this specific module, other publications support that course content learned through TBL correlates with higher scores on examinations.